2019
DOI: 10.1002/ppul.24469
|View full text |Cite
|
Sign up to set email alerts
|

Central sleep apnea in children with obstructive sleep apnea syndrome and improvement following adenotonsillectomy

Abstract: Background Although the pathogenesis of central and obstructive events seems to be different, these two entities may somehow be related. We aimed to determine whether, as reported in previous research, the number of central sleep apnea (CSA) cases in a population of children with obstructive sleep apnea syndrome (OSAS) was greater than in patients without obstructive events, and if CSA worsens with increasing OSAS severity. As a second objective, we analyzed changes in central apnea index (CAI) after adenotons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…We found that the TS21 individuals with a CAI > 2/h also had greater OAHI values (Table 2). These results indicate that upper airway obstruction may be linked to central apnea in Down syndrome, as previously described in the general population of children with OSA 21 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We found that the TS21 individuals with a CAI > 2/h also had greater OAHI values (Table 2). These results indicate that upper airway obstruction may be linked to central apnea in Down syndrome, as previously described in the general population of children with OSA 21 …”
Section: Discussionsupporting
confidence: 83%
“…These results indicate that upper airway obstruction may be linked to central apnea in Down syndrome, as previously described in the general population of children with OSA. 21 In our study, we found that CSA was more frequent in TS21 subjects younger than 2 years of age independently of biological sex.…”
Section: Sex-related Differences In Central Breathing Abnormalitiessupporting
confidence: 51%
“…Camacho and colleagues reported that with increasing severity of OSA, there was an associated increase in CAI. 18 Our results show there was significantly greater severity of OSA when CAI was greater than 5 in the OSA + CSA group. The key differences between Camacho and colleagues and our study were that we included children with neurological abnormalities, and we had separated our groups into OSA only with CAI <1, and subdivided groups of OSA + CSA into different levels of CAI, because there is not a general consensus in literature on the cutoff for CSA.…”
Section: Discussionmentioning
confidence: 45%
“…While our cohort is limited, 2 out of 21 patients (9.5%) had an elevated central apnea index which is more common than is reported in the general population, and both these patients were older than 2 years 16,22–26 . In both cases, central events were only ~33% of events which may reflect a reflex apneic pause following upper airway obstruction, subsequent deep inspiration, and pulmonary stretch receptor response (Hering‐Breuer reflex) rather than a central pathologic process 27–30 . Further studies are needed to delineate the true prevalence of central sleep apnea in SYS given the limited number of patients available for this study.…”
Section: Discussionmentioning
confidence: 84%